Tourism workers' resilience in Siem Reap during COVID-19 - Michele Ford; Soksamphoas Im (Annals of Tourism Research Empirical Insights, 2023)
This article identifies factors influencing hotel and guesthouse workers' coping strategies during COVID-19 in Cambodia's premier tourist destination, Siem Reap. Drawing on qualitative data including 135 semi-structured interviews conducted between March 2022 and March 2023, we found that individual characteristics, dense community networks and government interventions did strengthen hotel and guesthouse workers' capacity to cope with the economic shock caused by the pandemic. Importantly, however, a series of deeper structural issues - most notably the structure of the labour market, the unevenness of social security coverage and pre-existing debt - greatly undermined their capacity to exercise resilience. As these findings suggest, it is necessary to look beyond individual traits and behaviours, and even community-level structures, if we are to truly understand community resilience.
Keywords: 330; Hospitality; Resilience; Coping strategies; Debt; Social security; Cambodia